Impact of lithium pellets on plasma performance in the ASDEX Upgrade all-metal-wall tokamak. (17th November 2016) - Lang, P.T.; Maingi, R.; Mansfield, D.K.; McDermott, R.M.; Neu, R.; Wolfrum, E.; Arredondo Parra, R.; Bernert, M.; Birkenmeier, G.; Diallo, A.; Dunne, M.; Fable, E.; et al.
Abstract: The impact of lithium (Li) on plasma performance was investigated at the ASDEX Upgrade tokamak, which features a full tungsten wall. Li pellets containing 1.6 × 10 20 Li atoms were launched with a speed of 600 m s −1 to achieve deep penetration into the plasma and minimize the impact on the first wall. Homogeneous transient Li concentrations in the plasma of up to 15% were established. The Li sustainment time in the plasma decreased with an increasing heating power from 150 to 40 ms. Due to the pellet rate being restricted to 2 Hz, no Li pile-up could take place. No significant positive impact on plasma properties, as reported from other tokamak devices, could be found; the Li pellets rather caused a small reduction in plasma energy, mainly due to enhanced radiation. Due to pellet injection, a short-lived Li layer was formed on the plasma-facing components, which lasted a few discharges and led to moderately beneficial effects during plasma start-up. Most pellets were found to trigger type-I ELMs, either by their direct local perturbation or indirectly by the altered edge conditions; however, reliability was less than 100%.